Identification of central mechanisms underlying anorexigenic effects of intraperitoneal L-tryptophan. Issue 15 (17th October 2018) - Gartner, Sarah N.; Klockars, Anica; Prosser, Colin; Carpenter, Elizabeth A.; Levine, Allen S.; Olszewski, Pawel K.
Abstract : A free essential amino acid, L-tryptophan (TRP), administered through a diet or directly into the gut, decreases food intake by engaging neural mechanisms. The ability of intragastric TRP to cross into the general circulation and through the blood–brain barrier, at least partly underlies hypophagia. It is unclear although, whether TRP's anorexigenic effects and accompanying neural processes occur in the absence of the initial action of TRP on the gut mucosa. Here, we addressed this issue by using a fundamental approach of examining effects of intraperitoneally administered TRP on feeding and neuronal activation in rats. We found that 30 mg/kg, intraperitoneal, TRP decreases deprivation-induced intake of standard chow and thirst-driven water intake. A 100 mg/kg dose was necessary to suppress consumption of palatable chow and of sucrose and saccharin solutions in nondeprived animals. Intraperitoneally TRP did not induce a conditioned taste aversion; thus, its anorexigenic effects were unrelated to sickness/malaise. c-Fos mapping in feeding-related brain sites revealed TRP-induced changes in the dorsal vagal complex, hypothalamic paraventricular and supraoptic nuclei and in the basolateral amygdala. TRP enhanced activation of hypothalamic neurons synthesizing an anorexigen, oxytocin (OT). Pharmacological blockade of the OT receptor with a blood–brain barrier -penetrant antagonist, L-368, 899, attenuated TRP-induced decrease in deprivation-induced chow intake, but not in thirst-driven water consumption. We conclude that TRP triggers anorexigenic action and underlying neural responses even when it does not directly contact the gut mucosa. TRP requires OT to decrease energy intake, whereas OT is nonobligatory in TRP's effects on drinking behavior.